'The reader–viewer' in Indian literate-media contexts: A Kerala archive. Issue 2 (1st December 2015) - Balakrishnan, Kavitha
This article discusses a Kerala archive of periodical magazines (1900–2012), an Indian region's approach to the print-picture practices of periodical magazines within the context of twentieth-century literate media. It outlines a few characteristic contexts of the Malayali reader using his unarticulated flip side, the Malayali viewer. This is an image-rich story of a range of print-picture genres, a visual field of literary illustrators, cartoonists, graphic authors, calligraphic title and film poster designers and photo-featurists as they have culturally functioned in the mindscapes of a reading/looking class. The literary illustrators among them bear the problematic title of 'aesthetic viewing' in an ephemeral domain. Their story is presented on the basis of an extensive archival research into discreet cultural hegemony and patriarchy in this region.